2017
DOI: 10.1071/he16052
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to participation in workplace health promotion (WHP) activities: results from a cross‐sectional survey of public‐sector employees in Tasmania, Australia

Abstract: Issue addressed Workplaces are promising settings for health promotion, yet employee participation in workplace health promotion (WHP) activities is often low or variable. This study explored facilitating factors and barriers associated with participation in WHP activities that formed part of a comprehensive WHP initiative run within the Tasmanian State Service (TSS) between 2009 and 2013. Methods TSS employee (n=3228) completed surveys in 2013. Data included sociodemographic characteristics, employee-perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 36 publications
7
37
0
Order By: Relevance
“…The most common reasons for participating in the pilot of the Activity for Well-Being program were related to a desire to improve health, while the most common reason for not participating was related to time constraints. These findings are consistent with previous studies such as the Step It Up Challenge, a workplace physical activity intervention in New Zealand, that reported the most prevalent reasons for participating in the program were associated with a desire to improve health and fitness (Davey et al, 2009); and the Healthy@Work program, a Tasmanian study that found timeand health-related factors were associated with lower levels of participation (Kilpatrick et al, 2017). Qualitative and survey data from the current project indicated that the actual modes of recruitment used (i.e., emails, flyers, and presentations at team meetings) were appropriate; however, there was a need for more promotion through multiple sources, including promotion over a longer period of time and better education around the nature of the program, particularly in residential settings.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The most common reasons for participating in the pilot of the Activity for Well-Being program were related to a desire to improve health, while the most common reason for not participating was related to time constraints. These findings are consistent with previous studies such as the Step It Up Challenge, a workplace physical activity intervention in New Zealand, that reported the most prevalent reasons for participating in the program were associated with a desire to improve health and fitness (Davey et al, 2009); and the Healthy@Work program, a Tasmanian study that found timeand health-related factors were associated with lower levels of participation (Kilpatrick et al, 2017). Qualitative and survey data from the current project indicated that the actual modes of recruitment used (i.e., emails, flyers, and presentations at team meetings) were appropriate; however, there was a need for more promotion through multiple sources, including promotion over a longer period of time and better education around the nature of the program, particularly in residential settings.…”
Section: Discussionsupporting
confidence: 90%
“…An Austrian study by Nöhammer et al (2010) noted that having easy and regular access to information and being personally notified may increase employee participation in workplace health promotion. Other studies have shown that perceived management support for such programs contributes to employee participation (Sloan and Gruman, 1988;Kilpatrick et al, 2017). Similarly, management support has previously been identified as impacting the implementation process for worksite health promotion programs (Wierenga et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As mentioned, there are no published studies focusing on the workplace barriers to lifestyle change specific to preconception, pregnant, and postpartum working women. However, general barriers include: heavy workloads, health promotion activity scheduling and location, work patterns such as part-time work or shift work, workplace location, limited availability of healthy lifestyle activities [28], and unsupportive management [29]. Additional obstacles impacting pregnant and postpartum women underscore the importance of tailored health promotion for this population, including health concerns such as gestational diabetes or morning sickness; short interconception periods, which may not be long enough to return to a healthy weight; and children's health problems [30].…”
Section: Barriers To Workplace Health Promotionmentioning
confidence: 99%
“…However, there are barriers that must be overcome in order to establish a successful industry/academia/community collaboration (Kilpatrick et al, 2017).…”
Section: Creating Synergies Among All Stakeholders To Strengthen Wellmentioning
confidence: 99%